THE JOURNEY OF CORALINE JONES: A HERO'S JOURNEY ANALYSIS OF CORALINE (2002) - Achmad Rizky Nur Pratama, - (2021)
The journey of a character in becoming the hero or the savior of the story seems to be an important element of many literary works. Furthermore, a heroic story is able to entertain and serve as a role model for children. Thus, this research was conducted to analyze the journey of the main character in becoming the hero in a children's novella. The character that was analyzed in this research is Coraline Jones from Coraline (2002) by Neil Gaiman. In order to analyze Coraline's journey and determine her character archetype, the Hero's Journey Theory (Vogler, 2007) was utilized. The result shows that Coraline's journey seems to follow the traditional Hero's Journey pattern, making it a prime example of a hero's journey story. This research also discussed the type of hero Coraline is which leads to a conclusion that Coraline can be considered as an unwilling hero. Furthermore, Coraline's heroic and inspiring characteristics seem to balance the dark fantasy elements of the novella, making it much more enjoyable for children.